Implementasi Manajemen Kurikulum Berbasis Nilai-Nilai Islam Moderat dalam Penguatan Karakter Peserta Didik di Madrasah - Jenny Fransiska; Yusman Haris; Didi Kosmanto; ,Lukman Asha; Jumira Warlizasusi; Irwan Fathurrochman; Destriani (Institut Kariman Wirayudha Sumenep, 2026)
This study focuses on the implementation of curriculum management based on moderate Islamic values ​​as a strategy for strengthening student character in madrasas, a crucial issue amidst rising intolerance and a weakening culture of inclusiveness in educational settings. Although several previous studies have highlighted the importance of religious moderation in Islamic education, studies that comprehensively integrate moderation with curriculum management are still limited. This study aims to describe and analyze how the values ​​of tawasuth, tasamuh, tawazun, and i'tidal are integrated through curriculum planning, implementation, and evaluation in madrasas. Informants consisted of the madrasah principal, the deputy head of curriculum, Islamic Religious Education teachers, and students selected through purposive sampling. Data were collected through semi-structured interviews, observations, and document analysis. The research instruments included interview guides, observation sheets, and document analysis formats that were validated through triangulation of sources and techniques. The results indicate that moderate curriculum management is able to direct a dialogic, collaborative, and inclusive learning process, and results in significant improvements in student character, particularly in terms of tolerance, empathy, and the ability to engage in polite dialogue. These findings suggest that religious moderation is an effective foundation for curriculum development and can serve as a preventative mechanism against intolerance and radicalism in madrasahs. This research emphasizes the need for strengthening teacher capacity, leadership support, and a conducive institutional ecosystem to ensure the sustainable implementation of a moderate Islam-based curriculum